Exploring Employee Expectations and Acceptance of a Generative AI HR Chatbot : A Case Study on Digital HR Services - Niemistö, Emilia (My University, 2025)
Generative artificial intelligence has increasingly grown in popularity during the past few years and its use in organizations has become more valuable. Generative artificial intelligence chatbots are a prominent example of the use of artificial intelligence that can interact with users in a way that resembles human interaction. In organizations, generative artificial intelligence chatbots can streamline many business processes including human resources processes and increase employees’ user experience. Human resource chatbots can handle repetitive tasks, allowing human resource teams to focus on more strategic work as well as provide employees with autonomy to access information and support quickly and efficiently. This research is a case study exploring employee perceptions and expectations regarding digital human resource services, focusing on the integration of a generative artificial intelligence powered assistant. Through interviews this research aims to identify which human resource tasks could be self-service for employees and which must remain as tickets. In addition, the aim is to understand in which situations employees seek human resource assistance and determine the role and reliability of the artificial intelligence assistant and whether it is welcomed by employees. The research is a qualitative case study. Data was gathered by interviewing human resource personnel and employees of the case company. The interviews focus on employees’ expectations and perceptions of the digital human resource services and artificial intelligence assistant as well as their possibilities from a self-service viewpoint. The interviews were transcribed and analyzed by using thematic analysis. The main findings of the interviews with employees show that employees have varying expectations regarding the artificial intelligence assistant. Most interviewees expect fast support and easy access to human resource information. The interviewees have concerns about privacy and response reliability. Acceptance of the artificial intelligence assistant highly depends on accurate responses, trust and peer-encouragement. The main findings of the interviewees with human resource personnel show that the artificial intelligence assistant is believed to save both employees time and reduce human resource personnels workload. The importance of training to effectively use the artificial intelligence assistant and communicating about its purpose was emphasized. However, while artificial intelligence was seen as helpful, human touch was still recognized as an essential part of human resource support. Based on the results it is recommended to make sure that employees know how to use the artificial intelligence assistant and consider user concerns to enhance trust. It is also important to ensure that the artificial intelligence assistant works properly and provides high quality answers to avoid frustration among users. Feedback should be used to continuously improve the assistant. Additionally, maintaining the option to discuss with human resource personnel is valuable.

Generatiivisen tekoälyn suosio on kasvanut viime vuosina nopeasti ja sen käyttö organisaatioissa on tullut yhä arvokkaammaksi. Generatiiviseen tekoälyyn perustuvat chatbotit ovat merkittävä esimerkki tekoälyn käytöstä, sillä ne voivat olla vuorovaikutuksessa käyttäjien kanssa tavalla, joka muistuttaa ihmisten välistä vuorovaikutusta. Organisaatioissa generatiiviseen tekoälyyn perustuvat chatbotit voivat tehostaa monia liiketoimintaprosesseja, mukaan lukien henkilöstöhallinnon prosessit, sekä parantaa työntekijöiden käyttäjäkokemusta. Henkilöstöhallinnon chatbotit voivat hoitaa toistuvia tehtäviä, jolloin henkilöstöhallinnon tiimit voivat keskittyä strategisempiin töihin sekä tarjota työntekijöille itsenäisen pääsyn tietoihin ja tukeen nopeasti ja tehokkaasti. Tämä tutkimus on tapaustutkimus, joka tutkii työntekijöiden käsityksiä ja odotuksia digitaalisista henkilöstöhallinnon palveluista, keskittyen generatiiviseen tekoälyyn perustuvan avustajan käyttöönottoon. Haastattelujen avulla tavoitteena on tunnistaa, mitkä henkilöstöhallinnon tehtävät voisivat olla itsepalveluna työntekijöille ja mitkä tulisi edelleen käsitellä tikettijärjestelmän kautta. Lisäksi tavoitteena on ymmärtää, millaisissa tilanteissa työntekijät hakevat henkilöstöhallinnon tukea, sekä selvittää tekoälyavustajan rooli ja luotettavuus ja se, otetaanko se työntekijöiden keskuudessa hyvin vastaan. Tutkimus on kvalitatiivinen tapaustutkimus. Aineisto kerättiin haastattelemalla henkilöstöhallinnon henkilöstöä ja tapausyrityksen työntekijöitä. Haastattelut keskittyvät työntekijöiden odotuksiin ja käsityksiin digitaalisista henkilöstöhallinnon palveluista ja tekoälyavustajasta sekä niiden mahdollisuuksiin itsepalvelun näkökulmasta. Haastattelut litteroitiin ja analysoitiin temaattisen analyysin avulla. Haastattelujen tärkeimmät tulokset työntekijöiden kanssa osoittavat, että työntekijöillä on vaihtelevia odotuksia tekoälyavustajaa kohtaan. Suurin osa haastatelluista odottaa nopeaa tukea ja helppoa pääsyä henkilöstöhallinnon tietoihin. Haastateltavia huolettavat yksityisyys ja vastausten luotettavuus. Tekoälyavustajan hyväksyntä riippuu vahvasti vastausten tarkkuudesta, luottamuksesta ja vertaisten rohkaisusta. Henkilöstöhallinnon henkilöstön haastattelujen tärkeimmät tulokset osoittavat, että tekoälyavustajan uskotaan säästävän sekä työntekijöiden aikaa että vähentävän henkilöstöhallinnon työkuormaa. Koulutuksen tärkeyttä tekoälyavustajan tehokkaaseen käyttöön sekä sen tarkoituksen viestimistä korostettiin. Vaikka tekoäly nähtiin hyödyllisenä, inhimillinen kosketus tunnistettiin silti keskeiseksi osaksi henkilöstöhallinnon tukea. Tulosten perusteella suositellaan varmistamaan, että työntekijät tietävät, miten tekoälyavustajaa käytetään, ja huomioimaan käyttäjien huolenaiheet luottamuksen lisäämiseksi. On myös tärkeää varmistaa, että avustaja toimii kunnolla ja antaa korkealaatuisia vastauksia turhautumisen välttämiseksi. Palautetta tulisi käyttää avustajan jatkuvaan kehittämiseen. Lisäksi mahdollisuus keskustella henkilöstöhallinnon henkilöstön kanssa on arvokasta säilyttää.
Keywords: chattibotit; generatiivinen tekoäly; henkilöstöhallinto; kielimallit; käyttäjäkokemus; fi=Tietojärjestelmätiede|en=Information Systems|; Master’s Programme in Computing Sciences